Mental health of the multidisciplinary team of the Psychosocial Care Center during coping with work-related crises (Research, Society and Development, 2021)
To analyze the characteristics of crises that can occur with the multidisciplinary team that works at the Psychosocial Care Center (CAPS) and how much this can affect the mental health and daily work activities of these professionals. This is a theoretical and reflective essay with descriptive characteristics, proposed after the observation of dynamics in the practices of mental health services. The reflection was based on the results of searches in Brazilian legislation governing mental health care, articles from journals specializing in health sciences in general, mental health, psychiatry and public health, as well as books in the areas described and authors, considered specialists. with extensive theoretical and scientific production. Professionals become vulnerable to unresolved stressful events in the workplace, so mental illness is a possibility when managers and society do not realize the workers' needs, ignoring their complaints and notes. In situations where a member of the multidisciplinary team demonstrates negative attitudes and behaviors, it is likely affecting other colleagues, creating a harmful and toxic environment for the team and hindering the work process for the recovery of the patient and family. More studies and research in this area are still needed, as few articles have emphasized the mental health of the CAPS team, little is written about the suffering of professionals working in mental health units. There is little appreciation of this topic, it is implicit that health workers do not get sick, nor do they have needs, just assist the patient in distress.